Research on Teaching Reform of Audit Practice and Cases Based on OBE Concept under the Background of "Internet plus" - Dai, Chenchen; Nie, Xiaopeng (International Journal of Social Sciences and Public Administration, 2023)
The implementation of talent training objectives and graduation requirements under the OBE concept depends on the teaching design and implementation of each course. In the information age, integrating "Internet plus" into the curriculum teaching design under the OBE concept is conducive to the innovation and implementation of teaching design. Based on the concept of "Internet + OBE", the course "Audit Practice and Cases" reforms teaching from the aspects of teaching design, teaching evaluation, teaching methods, etc., trying to change the "teacher centered" teaching method, the traditional "full room" teaching form of teachers, change the teaching content limited to textbooks, realize the digitalization, intelligence and grid of teaching, improve teaching efficiency, and cultivate students’ comprehensive learning ability, Adapt them to the needs of economic development in the new era.